TEACHER-STUDENT RELATIONSHIP: REFLECTION ON THE QUALITY OF CHARACTER EDUCATION IN ISLAMIC BOARDING SCHOOLS (CASE STUDY AT NURUL WAFA ISLAMIC BOARDING SCHOOL, DEMUNG-BESUKI) - Syaifullah, Syaifullah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study uses the Teacher Student Relationship method to determine the cultivation of character and quality improvement of character education for students at the Nurul Wafa Islamic Boarding School. This study uses a qualitative approach. Data collection techniques in this study were carried out circularly using three approaches: l) participant observation, 2) in-depth interviews, and 3) documentation. While the data analysis in this study was carried out through; data reduction, data presentation, and drawing conclusions or verification. The results of this study show that cultivating character using the Teacher Student Relationship method at Pondok Pesantren Nurul Wafa Demung, Besuki, Situbondo can have a positive impact on instilling character with Harmonization of Internal and External Communication, Delegation of Authority, and Mutual Relationship as a step in building quality character education to students.